Periodic Property and Asymptotic Behavior for a Discrete Ratio-Dependent Food-Chain System with Delays - Changjin Xu; Peiluan Li; Maoxin Liao (Discrete Dynamics in Nature and Society)
In this paper, a discrete ratio-dependent food-chain system with delay is investigated. By using Gaines and Mawhin’s continuation theorem of coincidence degree theory and the method of Lyapunov function, a set of sufficient conditions for the existence of positive periodic solutions and global asymptotic stability of the model are established.